1982
DOI: 10.1017/s002185960005437x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of water balance of dryland wheat through the use of chlormequat chloride

Abstract: In field trials made for two years in the dry period of a semi-arid tract under natural precipitation at the Indian Agricultural Research Institute, New Delhi, overnight seed-soaking of wheat in 0-5 % solution of 2-chloro-ethyl-trimethyl ammonium chloride (CCC) prior to sowing increased the grain yield. When treated with foliar application of the chemical in concentrations ranging between 40 and 1000 mg/1, wheat plots yielded better than did the untreated control, but no consistency was noted between the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
3
15
0
1
Order By: Relevance
“…However, root characteristics including root length, density and branching, have not been unequivocally associated with water uptake and yielding capacity in cereals (Hamblin and Tennant 1987, Comfort et al 1988, Mian et al 1994). There are some indications in the literature that while reducing shoot growth, antigibberellic PGRs may simultaneously improve root growth and performance (De et al 1982, Cooke et al 1983, Bragg et al 1984, Yang and Naylor 1988, Webb and Fletcher 1996, though reports indicating yield improvement with PGR induced change in root growth are rare (De et al 1982). In some cases PGR applications improved root to shoot ratio by reducing above ground growth (Enam andCartwright 1990, Rajala and.…”
Section: Root Growthmentioning
confidence: 99%
“…However, root characteristics including root length, density and branching, have not been unequivocally associated with water uptake and yielding capacity in cereals (Hamblin and Tennant 1987, Comfort et al 1988, Mian et al 1994). There are some indications in the literature that while reducing shoot growth, antigibberellic PGRs may simultaneously improve root growth and performance (De et al 1982, Cooke et al 1983, Bragg et al 1984, Yang and Naylor 1988, Webb and Fletcher 1996, though reports indicating yield improvement with PGR induced change in root growth are rare (De et al 1982). In some cases PGR applications improved root to shoot ratio by reducing above ground growth (Enam andCartwright 1990, Rajala and.…”
Section: Root Growthmentioning
confidence: 99%
“…Similar results have been observed on winter barley in Britain [24] . Soaking wheat seed in chlormequat led to a yield increase in arid land [28] and this effect has been attributed to increased root growth [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Soaking seed of winter oats in tetcyclasis restricted early internode elongation of the seedling and thereby improved winter hardiness [2] . Chlormequat applied to wheat seed produced modifications to growth which persisted through to harvest and led to increased yield [3,8,13] . In barley, seed application of mepiquat chloride with ethephon led to an increased number of ears per plant [31] .…”
Section: Introductionmentioning
confidence: 99%
“…One is that a reduction in the leaf area caused by onium compounds reduces the transpirational surface, which in turn reduces water loss . In addition to the reduction in leaf area, it has been shown that CCC can induce stomatal closure which would reduce transpiration (Misbra and Pradhan 1972;Pill et al 1979;De et al 1982). Another possibility which has been suggested is that treatment with onium compounds causes an accumulation of solutes, such as amino acids and sugars, which allows plants to maintain turgor under reduced leaf water potentials (Bode and Wild 1984;Knapp et al 1987).…”
Section: Gibberellin Biosynthesis Inhibitorsmentioning
confidence: 99%